Analysis of Prestress Loss and Structural Performance of Box-Type Prestressed Concrete Girders on the Cakung Flyover - Aldo Dion Selvistre; Viona Yeni; Putut Keswardi (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
The increasing traffic congestion in East Jakarta, particularly at the Cakung intersection, prompted the construction of the Cakung Flyover, designed with a prestressed concrete box-girder system. However, field observations revealed several serviceability issues, including hairline cracks (0.10–0.28 mm), vertical deflections of 18–25 mm, and a 30.5 % reduction in effective prestress compared with theoretical design values. This research aimed to analyze prestress losses and their structural implications through an integrated analytical–empirical approach combining field measurements, theoretical modeling, and validation using SAP2000 and MATLAB simulations. The results showed that the box-girder section (A = 5.65 m², Wa = 5.43 m³, Wb = 2.76 m³) exhibited satisfactory flexural rigidity but experienced frictional losses at tendon angular deviations, particularly near anchorage zones. The tropical environment—average temperature 33 °C and relative humidity 85–90 %—accelerated creep, shrinkage, and relaxation in the 7-wire low-relaxation strands. Consequently, measured prestress losses were 1.3–1.6 times higher than those predicted by standard codes. This study confirms that tropical humidity significantly amplifies prestress degradation and highlights the need for climate-specific calibration of SNI 2847:2019 coefficients. The research contributes a calibrated correlation between tendon eccentricity (eₛ ≈ 1.195 m), deflection, and stress relaxation, enabling more accurate prediction and control of structural performance. The proposed framework provides practical guidelines for tendon configuration, prestress monitoring, and maintenance strategies for prestressed concrete flyovers in humid tropical regions such as Jakarta.